Desde las raíces: the intersection of indigeneity, language, and territorial belonging in the migration experience of a Tlapaneco immigrant in northeastern Kansas - Ramirez Quimbayo, Maria Camila (My University, 2026)
Negotiation of Indigenous identity and multilingual practices occur dynamically in the context of migration to the United States. Although Latin American immigrants are often categorized under broad labels such as "Latino" or "Hispanic", these classifications tend to obscure the unique experiences and linguistic repertoires of Indigenous communities. Drawing on a qualitative case study of a Tlapaneco immigrant from Guerrero, Mexico, currently residing in Northeastern Kansas, this research examines how Indigeneity, territorial attachment, and language intersect in the participant's migration experience. Data collection methods include a semi-structured narrative interview and a picture-naming task designed to capture lexical choices across the participant’s linguistic repertoire. The results show that Tlapaneco identity is actively maintained through enduring connections to community and territory, while the participant strategically mobilizes his multilingual repertoire across domains: Tlapaneco functions as cultural and symbolic capital, whereas Spanish and English serve as economic, social, and institutional resources. The findings also highlight how institutional language hierarchies and racialized migration dynamics contribute to the marginalization and reclassification of Indigenous identities within broader Latino categories. Taken together, this study contributes to understanding the complex ways in which language, migration, and institutional structures shape Indigenous identity in diasporic contexts by centering the narrative of a Tlapaneco immigrant.
Keywords: Intersectionality; Indigeneity; Territoriality; Language; Ethnicity; Migration